UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA DENGAN MODEL DIGITAL STORYTELLING PADA MATERI KEKAYAAN BUDAYA INDONESIA KELAS IV SDN TANAH TINGGI 09 JAKARTA PUSAT - Fitra Putri Kusuma; Julius Sagita; Indah Trismawanti (STKIP Subang, 2023)
The purpose of this study was to improve students' speaking skills in social studies class IV at SDN Tanah Tinggi 09 Central Jakarta. The type of research conducted was classroom action research which was carried out in 2 cycles. The learning model used in this research is Digital Storytelling (DST). The instruments used in improving the achievement of research are teacher activity observation sheets, student activity observation sheets, interviews and documentation. The conclusion of the research that has been done shows that there is an increase in the speaking skills of students after applying the Digital Storytelling model. This can be seen from the completeness of teacher and learner activities above 80%. In cycle I, the teacher's activity was 74% which in cycle II increased to 81.5%. In the activity of students in cycle I, it was 75%, which in cycle II increased to 85%. From the observation data obtained in the learning process, a model is needed that can motivate students to improve students' speaking skills.